2017
DOI: 10.1007/s00792-017-0963-x
|View full text |Cite
|
Sign up to set email alerts
|

Halophilic viruses with varying biochemical and biophysical properties are amenable to purification with asymmetrical flow field-flow fractionation

Abstract: Viruses come in various shapes and sizes, and a number of viruses originate from extremities, e.g. high salinity or elevated temperature. One challenge for studying extreme viruses is to find efficient purification conditions where viruses maintain their infectivity. Asymmetrical flow field-flow fractionation (AF4) is a gentle native chromatography-like technique for size-based separation. It does not have solid stationary phase and the mobile phase composition is readily adjustable according to the sample nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 50 publications
(104 reference statements)
2
27
0
Order By: Relevance
“…The obtained yield and purity (specific infectivity value for the virus peak was ~9 × 10 11 PFU/A 280 ) were comparable to those previously reported [ 5 ]. Good recovery of prokaryotic viruses with various biophysical properties after AF4 purification has also been reported previously [ 38 , 39 ].…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The obtained yield and purity (specific infectivity value for the virus peak was ~9 × 10 11 PFU/A 280 ) were comparable to those previously reported [ 5 ]. Good recovery of prokaryotic viruses with various biophysical properties after AF4 purification has also been reported previously [ 38 , 39 ].…”
Section: Resultssupporting
confidence: 72%
“…Our recent AF4-multi-angle light-scattering measurement (MALS) study showed that ultracentrifugation-based purification of φ6 yields virus specimen that has a relatively homogenous size distribution and little aggregates [ 5 ]. Virus-sized particles are generally well retained in the AF4 channel and elute at low cross-flow rates [ 5 , 38 , 39 , 45 ]. When compared to our previous study on φ6 that was performed with a thicker 350 μm spacer and resulted in virus elution at the end of the cross-flow gradient [ 5 ], here the thinner spacer promoted virus elution at higher cross-flow rates (peak maxima at a cross-flow rate of ~0.25 mL/min), providing improved resolution between monomeric viruses and putative larger sample components that are present if purification is performed with less purified inputs such as lysates or virus precipitates [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perpendicular to the laminar channel flow, a second flow (cross flow) and an electric field are applied simultaneously thereby inducing separation of sample constituents by size and charge ( Figure S1 ). Besides offering high-resolution separation and access to particle size distribution and surface charge (Zeta potential) of a respective sample, the possibility to purify (i.e., to remove matrix components smaller than the molecular weight cutoff of the ultrafiltration membrane via the cross flow) and separate matrix components from the analyte of interest renders EAF4 (just like AF4) a promising tool for an online purification of complex biological samples prior to further multi-detector analysis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%